1998
DOI: 10.2527/1998.763808x
|View full text |Cite
|
Sign up to set email alerts
|

Lowering the dietary calcium to total phosphorus ratio increases phosphorus utilization in low-phosphorus corn-soybean meal diets supplemented with microbial phytase for growing-finishing pigs.

Abstract: Crossbred growing-finishing pigs (n = 120) were used to investigate the effect of three dietary Ca:total P (tP) ratios (1.5:1, 1.3:1, or 1.0:1) on P utilization in low-P corn-soybean meal diets supplemented with microbial phytase at 500 phytase units/kg. The basal grower (23 to 54 kg BW) diet contained .39% tP including .07% added inorganic P (iP), and the basal finisher (54 to 123 kg BW) diet contained .32% tP without added iP. An adequate-P positive control diet without phytase supplementation contained .60%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
77
3
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(87 citation statements)
references
References 16 publications
5
77
3
1
Order By: Relevance
“…The efficacy of A. niger phytase in corn and soybeanmeal-based diets was mitigated at high dietary Ca:P ratios (Lei et al 1994;Liu et al 1998). Similarly, the beneficial effects of a P. lycii phytase on reducing faecal P excretion, observed when the Ca:P ratio in the diet was 1.15:1, was no longer evident when added to a diet with a ratio of 1.85:1 (Brady et al 2002).…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…The efficacy of A. niger phytase in corn and soybeanmeal-based diets was mitigated at high dietary Ca:P ratios (Lei et al 1994;Liu et al 1998). Similarly, the beneficial effects of a P. lycii phytase on reducing faecal P excretion, observed when the Ca:P ratio in the diet was 1.15:1, was no longer evident when added to a diet with a ratio of 1.85:1 (Brady et al 2002).…”
mentioning
confidence: 81%
“…1 were older. Lei et al (1994) however, found a depressive effect of dietary Ca level on phytase activity in weanling pigs, and Liu et al (1998) showed that P utilization in growing-finishing pigs in the presence of phytase was improved at a Ca:P ratio of 1 rather than 1.5, indicating that age does not affect this response. The inhibitory effect of Ca on phytase efficacy was shown to be less at pH 2.5 than at pH 6.5; probably because of decreased solubility of the complex at the higher pH (Tamin et al 2004).…”
Section: Phosphorusmentioning
confidence: 99%
“…Growth improvement by lowering the Ca to NPP ratio results from the increase in phytase activity, P digestibility, and P retention in broiler chickens (Qian et al, 1997), turkeys (Qian et al, 1996), and pigs (Liu et al, 1998;Stein et al, 2011). Lowering the dietary Ca to NPP ratio also increases the absorbed and retained P (Al-Masri, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…The P recommendations of several universities were 10 to 20% and of industries were 20 to 30% above the 1988 NRC requirements (Cromwell 1989), and P concentrations in sow and finisher pig diets were 40 to 55% above these requirements (Spears 1996). Pigs fed commercial feeds excrete 50 to 80% of P intake (Kornegay and Harper 1997), and faecal P excretion increased with increasing dietary P Liu et al 1998); thus, a portion of P excreted by pigs results directly from feeding excessive levels of P. Therefore, reducing excessive P levels in diets may markedly reduce P excretion.…”
mentioning
confidence: 99%